Return to sport among French Alpine skiers after an anterior cruciate ligament rupture: Results from 1980 to 2013 - Haida, A.; Coulmy, N.; Dor, F.; Antero-Jacquemin, J.; Marc, A.; Ledanois, T.; Tourny, C.; Rousseaux-Blanchi, M. P.; Chambat, P.; Sedeaud, A.; Toussaint, J.-F. (The American Journal of Sports Medicine, 2016)
Background: There is little known about return to sport and performance after anterior cruciate ligament (ACL) tear in high-level alpine skiers.